ANALISIS STRATEGI BISNIS UNTUK MENINGKATKAN KEUNGGULAN BERSAING PADA TOKO DUA-A - Hasniwati Pasulle; Marni Daun Kalua; Muh Sabir (CV. Adiba Aisha Amira, 2024)
This research aims to identify and analyze business strategies that can be implemented by Dua-A stores to increase their competitive advantage. To achieve this goal, the research method used is a descriptive method, data collection techniques used are interviews and questionnaires using the SWOT analysis instrument. The results of the research are that Toko Dua-A has sufficient business capital to be used as strength to increase the inventory capacity of Toko Dua-A, increase product added value, flexible pricing strategies, as well as evaluate business locations and employee training to create competitive advantages, provide employee training to deal with external threats and strengthening the company's internal strengths, and placing employees according to their skills and fields to reduce risks and increase operational efficiency. This research provides insight into developing strategies that suit the conditions and challenges faced by Toko Dua-A